English as Medium of Instruction (EMI) at Primary Schools in Indonesia: Challenges and Opportunities - Sukmawati, Ida Dian; Pujiani, Tri (English Education Study Program STKIP PGRI Pacitan, 2024)
English as a Medium of Instruction (EMI) method bloomed widely in the educational context as the impact of advanced globalization. Pros and cons emerge worldwide toward the implementation of this teaching method. A study of EMI on the primary level becomes interesting since the teachers are faced with double challenges. While teaching young learners with their unique characteristics is a big challenge, they are required to teach the learners using an unfamiliar language which is English. Therefore, a descriptive-qualitative study was conducted to uncover this issue. Literature review, observation, and interviews with some teachers of international standard primary schools in Indonesia were employed to obtain comprehensive data on this issue. The result revealed many challenges and opportunities in the implementation of EMI at the primary level. This study suggests a better policy in the educational system shading the implementation of EMI in Indonesia and many supports are still needed.